Statistical Cost Analysis Re-Revisited: Reply - Griffin, James M. (Quarterly Journal of Economics, 1981)
Journal Article Statistical cost Analysis Re-Revisited: Reply Get access James M. Griffin James M. Griffin University of Houston Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 96, Issue 1, February 1981, Pages 183–187, https://doi.org/10.2307/2936150 Published: 01 February 1981